Diseño e implementación de una aplicación web de gestión de citas médicas e historias clínicas en el centro odontológico Odontoestetic - Rivadeneira Lema, Luis Eduardo (2024)
With the advancement in computer science and software development, it is currently unthinkable to work without the assistance of computer tools that simplify and speed up our work tasks. In the field of dentistry, the days of using paper and pencil to write prescriptions are long gone as a process methodology, all of this has been achieved thanks to the adaptation of software tools specifically designed to meet the needs of medical professionals, which has considerably improved the execution of their activities. Efficient management of medical appointments and management of medical records are critical aspects of modern dental care. In this context, the present work addresses the creation of a 'Medical Appointments and Clinical Records System' developed for the OdontoEstetic Dental Center. The problem lies in the absence of an integrated system that allows appointment booking, monitoring of electronic medical records and fluid communication between patients and dentists. Dental clinics still rely heavily on traditional methods, such as paper agendas and calls. telephone calls, which can lead to appointment scheduling errors, delays in care, and loss of important patient information. Given this situation, the need arises to develop an application for medical appointments and medical records designed specifically for dental clinics. This project's main objective is to provide a comprehensive technological solution that optimizes appointment management, improves the patient experience and makes work easier. For dental health professionals, the app will allow patients to conveniently book appointments on-site and doctors to access medical records from anywhere, anytime. Currently obtaining a result of easy access to the patients' agenda and clinical history, thus improving organization and personalized attention, which has generated greater customer and job satisfaction.